Effects of Pb(Mg1/3Nb2/3)O3 mixed-oxide modification on dielectric properties of Pb(Zr0.52Ti 0.48)O3 ceramics - Yimnirun R. (2014)
The dielectric properties of (1 - x)Pb(Zr0.52Ti 0.48)O3-(x)Pb(Mg1/3Nb2/3)O 3 (when x= 0, 0.1, 0.3, 0.5, 0.7, 0.9, and 1.0) ceramics prepared by an oxide-mixing method are determined by means of an automated dielectric measurement set-up. The dielectric constant and dielectric loss tangent of the ceramics are measured as functions of both temperature and frequency. The results indicate that the dielectric properties of the pure phase PZT and PMN are of normal and relaxor ferroelectric behaviors, respectively. The dielectric behaviors of the 0.9PZT-0.1PMN and 0.7PZT-0.3PMN ceramics are more of normal ferroelectrics, while the other compositions are obviously of relaxor ferroelectrics. However, with a higher degree of disorder the PMN-modified PZT shows more diffuse phase transition nature than the pure PMN. In addition, the transition temperature decreases and the maximum dielectric constant increases with increasing PMN content in the system. The rate of transition temperature change, however, depends significantly on the Zr/Ti ratio of PZT. © 2004 Elsevier B.V. All rights reserved.